Plagues upon the Earth: Disease and the Course of Human History - Rhode, Paul W. (Journal of Economic Literature, 2024)
Paul W. Rhode of University of Michigan and NBER reviews “Plagues upon the Earth: Disease and the Course of Human History” by Kyle Harper. The EconLit abstract of this book begins: “Explores the ways that human history has shaped disease ecology and pathogen evolution and how disease ecology and pathogen evolution have shaped human history in turn, detailing how the emergence, incidence, and consequences of disease in both individuals and populations are inseparable from a wider array of social and environmental factors.”